Avtonomna ureditev plačila za delo danes in jutri - sindikalni vidik - Toš Zajšek, Andreja (Podjetje in delo, 2018)
The scope of the "payment-for-work" institute and a number of other terms used as synonyms for the salary, often represents a basic, sometimes even the only, means of subsistence for workers themselves and their family. The salary agreement, which must always be in cash and other types of payments, if so provided by a collective agreement, is an essential element of the employment contract. The role of the social partners and the state is very important in regulating and determining the relationships between workers and employers in collective agreements. The social partners directly determine these relationships, and the state may encroach upon determining benefits from the workers` income, thus affecting its amount paid to the worker and ensuring effective legal protection of workers' rights.
Keywords: dodatki; osnovna plača; plača; plačilo za delo; prejemki iz delovnih razmerij